Characterization of a novel, ubiquitous fungal endophyte from the rhizosphere and root endosphere of Populus trees. (June 2017) - Vélez, Jessica M.; Tschaplinski, Timothy J.; Vilgalys, Rytas; Schadt, Christopher W.; Bonito, Gregory; Hameed, Khalid; Engle, Nancy; Hamilton, Cyd E.
Abstract: We examined variation in growth rate, patterns of nitrogen utilization, and competitive interactions of Atractiella rhizophila isolates from the roots of Populus hosts. Atractiella grew significantly faster on media substituted with inorganic nitrogen sources and slower in the presence of another fungal genus. To determine plausible causal mechanisms we used metabolomics to explore competitive interactions between Atractiella strains and Fusarium oxysporum or Leptosphaerulina chartarum . Metabolomic screening of potential microbial inhibitors showed increased levels of glycosides produced in vitro by Atractiella when grown with a different fungal genus, relative to when grown alone. Cumulatively, these results suggest Atractiella is a poor competitor with other fungi via direct routes e.g. faster growth rates, but may utilize chemical interactions and possibly nitrogen sources to defend itself, and niche partition its way to abundance in the plant host root and rhizosphere.